2011
DOI: 10.1073/pnas.1109739109
|View full text |Cite
|
Sign up to set email alerts
|

Social selection and peer influence in an online social network

Abstract: Disentangling the effects of selection and influence is one of social science's greatest unsolved puzzles: Do people befriend others who are similar to them, or do they become more similar to their friends over time? Recent advances in stochastic actor-based modeling, combined with self-reported data on a popular online social network site, allow us to address this question with a greater degree of precision than has heretofore been possible. Using data on the Facebook activity of a cohort of college students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
295
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(308 citation statements)
references
References 34 publications
12
295
0
1
Order By: Relevance
“…Recent advances suggest that, the human social behaviors present remarkable distinct properties against the differences in age, sex and personality etc., both on the collective and individual levels [42,[46][47][48]. Consequently, how to identify the evolution characteristics of online user preference with these attributes are still open questions, which requires not only the details of the user profiles but also the trade-off between the sample size and the statistical methods.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances suggest that, the human social behaviors present remarkable distinct properties against the differences in age, sex and personality etc., both on the collective and individual levels [42,[46][47][48]. Consequently, how to identify the evolution characteristics of online user preference with these attributes are still open questions, which requires not only the details of the user profiles but also the trade-off between the sample size and the statistical methods.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Online user preference could be affected by the social influence [8,41,42] and the recommendation systems [43][44][45]. Recent advances suggest that, the human social behaviors present remarkable distinct properties against the differences in age, sex and personality etc., both on the collective and individual levels [42,[46][47][48].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Contagion refers to the fact that as members of a friendship circle get married or have children, this behaviour is likely to encourage spread, putting social pressure or incentives on others within that group to move into the same life stage, alternatively to leave the group in order to affiliate with another (Christakis and Fowler, 2007). This distinction is related but not identical to the tendency of familiarity to breed similarity and vice versa: close people tend to become more similar over time (Lewis et al, 2012) and maintain friendships better with those who are similar (Burt, 2000;Tuma and Hallinan, 1979). Additionally, friendship itself is both selective and contagious: friendship networks may merge, so that people easier become friends with the friends of a friend, which further enhances the similarities between the original friend dyad (Wimmer and Lewis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…McGowan et al [6] also predicted churners from a telecommunications provider by experimenting with different dimensionality reduction and boosting methods. Lewis et al [5] examined Facebook networks of college students over a 4 year period and found an association between friendship maintenance and geographical proximity and shared tastes. Quercia et al [7] analysed Facebook friendships and users' personality traits, finding that churn was likely to happen if the ages of connected users differed and if one of the users was neurotic or introverted.…”
Section: Related Workmentioning
confidence: 99%